2012
DOI: 10.2146/ajhp110127
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist’s role in a Parkinson’s disease and movement disorders clinic

Abstract: A clinical pharmacist's regular involvement in an outpatient PD and movement disorders clinic has been well received by patients and clinic providers. The study results suggest that the pharmacist has made important contributions in areas such as therapeutic problem solving and medication education while freeing up providers for other responsibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Some studies have reported that the participation of a pharmacist in a multidisciplinary healthcare team promotes clinical benefits for PD patients and is considered a valuable healthcare strategy [ 14 , 15 ]. Medication therapy management (MTM) is one of the pharmacist’s duties, which consists of a service undertaken by the pharmacist in conjunction with other health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the participation of a pharmacist in a multidisciplinary healthcare team promotes clinical benefits for PD patients and is considered a valuable healthcare strategy [ 14 , 15 ]. Medication therapy management (MTM) is one of the pharmacist’s duties, which consists of a service undertaken by the pharmacist in conjunction with other health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating medication therapy management follow-up visits delivered by this clinic can address various medication-related issues and will help to evaluate the utility of this clinic for PD patients. A similar integrated care model has been well-described previously in the literature 8. Poon et al8 outlined the role of the CPS for PD patients in their medical center and described how pharmacist interventions made important contributions in areas such as therapeutic problem solving and medication education, allowing providers more time for other responsibilities.…”
Section: Discussionmentioning
confidence: 94%
“…A similar integrated care model has been well-described previously in the literature 8. Poon et al8 outlined the role of the CPS for PD patients in their medical center and described how pharmacist interventions made important contributions in areas such as therapeutic problem solving and medication education, allowing providers more time for other responsibilities. Future growth of the clinic could potentially incorporate clinical video telehealth to increase access to care to patients and caregivers from the nearest VA community-based outpatient clinics.…”
Section: Discussionmentioning
confidence: 94%
“…The information collected through PAPs represents an untapped source of clinical information that can be utilized to generate information on patient characteristics, patient outcomes, treatment adherence and reimbursement practices. Several studies have investigated patient outcomes with enrollment into PAPs [2][3][4][5][6][7]. Other reports of biologic PAPs for RA have presented dosing patterns [8].…”
Section: Introductionmentioning
confidence: 99%